2017
DOI: 10.2174/1381612822666160813214023
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Epidemiology: A Selective Review

Abstract: Background Globally, the most widely used set of compounds among the internationally regulated drugs is cannabis. Objective To review evidence from epidemiological research on cannabis, organized in relation to this field’s five main rubrics: quantity, location, causes, mechanisms, and prevention/control. Method The review covers a selection of evidence from standardized population surveys, official statistics, and governmental reports, as well as published articles and books identified via MEDLINE, Web of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 74 publications
3
29
0
2
Order By: Relevance
“…This may be attributed to cultural norms affecting prescribing physicians (i.e., cannabis is more likely to be offered to men), or to higher rates of requests for or compliance with this therapy, though this was not directly explored in our study. In any case, these data are in line with the findings of other epidemiologic studies, in which males were shown to be more inclined to use cannabis as a recreational drug [23-25] . …”
Section: Discussionsupporting
confidence: 91%
“…This may be attributed to cultural norms affecting prescribing physicians (i.e., cannabis is more likely to be offered to men), or to higher rates of requests for or compliance with this therapy, though this was not directly explored in our study. In any case, these data are in line with the findings of other epidemiologic studies, in which males were shown to be more inclined to use cannabis as a recreational drug [23-25] . …”
Section: Discussionsupporting
confidence: 91%
“…Currently, there are about 36.7 million active cannabis users in North America (Anthony et al, 2017). The legalization of cannabis in some states resulted in a gradual rise in the prevalence of cannabis use (Cerda et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This study’s investigation of geographical variations in cannabis incidence rates creates ‘benchmark values’ and should provide a useful foundation for a future extension of this line of epidemiological research on ‘place’ as a potential determinant of starting to use cannabis products. In a recent literature review, Anthony, Lopez-Quintero & Alshaarawy (2017) noted a lack of survey-based incidence estimates for cannabis use around the globe (2017). This study illustrates such estimation of incidence rates using publicly available national data.…”
Section: Discussionmentioning
confidence: 99%